Nursing administration in the geriatric department in the epidemic of COVID-19 - Hui Fan; Pei-Bei Duan; Cai-Yun Nie; Chun-Xia Ma (Wolters Kluwer Medknow Publications, 2020)
In order to strengthen the prevention and management in the geriatric department during the pandemic of COVID-19 and to explore how to implement nursing measures to control the spread of COVID-19 to elderly patients, our geriatric department established a leading group for epidemic prevention to train the medical staffs, the patients and caregivers and implemented a set of measures such as controlling the source of infection, cutting off the transmission route, and rehabilitation nursing of Chinese medicine, thus achieved zero infection of medical staff and elderly patients.